Aneurysm growth after late conversion of thoracic endovascular aortic repair - Hirofumi Kasahara; Ichiro Hayashi; Norimasa Haijima (SAGE Open Medical Case Reports, 2015)
A 69-year-old man underwent thoracic endovascular aortic repair of a descending aortic aneurysm. Three years later, he developed impending rupture due to aneurysmal expansion that included the proximal landing zone. Urgent open surgery was performed via lateral thoracotomy, and a Dacron graft was sewn to the previous stent graft distally with Teflon felt reinforcement. Postoperatively, four sequential computed tomography scans demonstrated that the aneurysm was additionally increasing in size probably due to continuous hematoma production, suggesting a possibility of endoleaks. This case demonstrates the importance of careful radiologic surveillance after endovascular repair, and also after partial open conversion.